Trilogy Development of Proopiomelanocortin Neurons From Embryonic to Adult Stages in the Mice Retina - Zhang, Xuhong; Wang, Xiaoyu; Wang, Senjie; Peng, Wei; Ullah, Rahim; Fu, Junfen; Zhou, Yudong; Shen, Ye (Frontiers in Cell and Developmental Biology, 2021)
POMC-positive amacrine cells (POMC-ACs) were first discovered in mouse retina in 2010; however, its development has not been studied yet. We bred POMC-EGFP mice to produce mouse pups and investigated the development of POMC-ACs from embryonic to adult stages. We found that the POMC-ACs development is mainly divided into three stages: the embryonic stage, the close-eye stage, and the open-eye stage. Each stage has unique characteristics. At the embryonic stage, POMC-ACs appeared in the retina at about E13. There was a developmental peak at E15, followed by an “E15-E16 cliff descent”. POMC-ACs showed increased soma and spine number at the close-eye stage and formed two bands of the inner plexiform layer (IPL) with a “firework model”. The developmental topographic map was “superiorly asymmetric,” which always existed in the inner layer but disappeared from the outer layer at about P6. At the same time, the outer layer distribution showed a “regularity peak”. At the open-eye stage, the development of POMC-ACs nearly stays stable with the widen IPL “long-necked,” which increased the soma-dendrite distance.